Application of h and h-type indices at meso level: A case of Malaysian engineering research - Muzammil, Tahira; Alias, Rose Alinda; Bakri, Aryati; Tahira, Muzammil; Alias, Rose Alinda; Bakri, Aryati (Malaysian Journal of Library and Information Science, 2017)
Tahira, M., Alias, R. A., & Bakri, A. (2015). Application of h and h-type indices at meso level: A case of Malaysian engineering research. Malaysian Journal of Library & Information Science, Vol.20, no. 3: 77-86. Quantity and quality of research publication productivity are the main areas of concern for the scientific community. The way of accountability of research performance evaluation has been changing with the advent of new metrics. The research performance evaluation clearly emphasizes on peer review approach. This approach possesses a central position in making an economic decision and monitoring of research and development programs of Higher Education Institutions. The combined use of various indicators is consistently recommended for Research Performance Evaluation (RPE). The study empirically examines and evaluates the feasibility of new RPE development by applying the h and h-type indices along with traditional metrics for the case of Malaysian Engineering Research at the meso level. This study helps in understanding the application of h and h-type indices and establishes that these indices are helpful in supporting and monitoring RPE and can be used along with traditional activity and impact metrics. Among the studied h-type indices, the revised development was found comparatively more meaningful with a less statistical error.